Neotypification of Urostachys vorwerkii (Lycopodiaceae) - Mazumdar, Jaideep (Phytotaxa, 2015)
Nessel (1934) first described the name Urostachys vorwerkii Nessel (1934: 178) (Lycopodiaceae) based on Himalayan specimen from unknown locality in India. But this name is largely overlooked in Indian literature.